Characterisation of the bacterial and archaeal microbiota in processed colostrum collected from a spring-calving dairy herd - Sabine Scully; Bernadette Earley; Paul E. Smith; Matthew S. J. Finnie; Catherine McAloon; David A. Kenny; Sinéad M. Waters (PLoS ONE, 2026)
Colostrum feeding is critical for neonatal calf health, providing immunoglobulins (Ig) and other bioactive compounds that support immune function and early microbiome development. While the microbiota of fresh colostrum has been characterised, colostrum on commercial dairy farms is often refrigerated and reheated prior to feeding – practices that may alter its microbial composition. Therefore, the objective of this study was to characterise the prokaryotic community of refrigerated and reheated (processed) colostrum collected immediately before calf feeding. Twenty-one processed colostrum samples were collected from a single, primi- and multiparous Holstein-Friesian and Jersey, spring-calving dairy herd with no more than two donors contributing to each sample. Colostrum samples were refrigerated for no more than 24h and then re-heated in a 38°C water bath for 60 minutes. Colostrum samples were collected immediately prior to being fed to the calf. Microbial DNA was extracted and16S rRNA gene amplicon libraries were sequenced using the Illumina platform. Raw sequencing data were processed in R via the DADA2 pipeline, and an amplicon sequence variant (ASV) table was generated. Taxonomy was assigned using the SILVA database (v. 138.1) and data were subjected to α- and β-diversity analysis using Phyloseq, Microbiome and Vegan . Breed and parity had no effect (P ≥ 0.05) on α- and β-diversity. The mean Shannon index score (α-diversity) was 2.26 (SE 0.18), indicating unevenness and low levels of richness. Microbial community composition varied considerably between samples. Five archaeal ASV genus groups were identified, with Methanobrevibacter dominating this community(relative abundance (RA) of 85.19%). Four bacterial phyla were identified as the major contributors to the bacterial component of processed colostrum. Only 39 ASV genus groups were identified as having a RA > 0.05%. Processed colostrum was dominated by Pseudomonas (RA = 20.97%) and Acinetobacter (RA = 18.65%). These genera, along with 11 others, including Romboutsia, Flavobacterium. Lachnospiraceae NK3A20 group and Clostridium sensu stricto 1 were present across all samples and thus considered core bacteria. Overall, these findings indicate that refrigeration and reheating may significantly alter the natural colostrum microbiota, reduce diversity and increase heterogeneity of the community composition. Further research is needed to determine how these changes influence microbial seeding and calf health outcomes.